2019
DOI: 10.1101/783423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of interferential stimulation of the human brain with electrode arrays

Abstract: Interferential stimulation (IFS) has generated considerable interest recently because of its potential to achieve focal electrical stimulation in deep brain areas despite applying currents transcranially. Conventionally, IFS applies sinusoidal currents through two electrode pairs with close-by frequencies.Here we propose to use two arrays of scalp electrodes with current intensity through each electrode optimized to target a desired location in the brain. We formulate rigorous optimization criteria for IFS to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Our study, for the first time, suggests that the idea of TI stimulation is plausible, not only in computational models and experiments on mice [27,[34][35][36][37][38], but also in actual experiments performed on healthy human participants. Since the idea of TI stimulation has been raised, the only in vivo investigations have been performed on mouse brains [27].…”
Section: Ti Stimulation Is Effective In the Human Motor Cortexmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study, for the first time, suggests that the idea of TI stimulation is plausible, not only in computational models and experiments on mice [27,[34][35][36][37][38], but also in actual experiments performed on healthy human participants. Since the idea of TI stimulation has been raised, the only in vivo investigations have been performed on mouse brains [27].…”
Section: Ti Stimulation Is Effective In the Human Motor Cortexmentioning
confidence: 79%
“…Based on the concept of TI stimulation, several modeling and computation studies have been performed to explore the feasibility of TI stimulation in the human brain but have revealed different results. Several studies reported that TI stimulation generated field strength in deep brain regions similar to tACS with smaller electric field intensity in superficial areas [34][35][36][37][38]. A computational modeling study explored the impact of TI stimulation on neuron levels but found that not all types of neurons responded to TI stimulation [39].…”
Section: Introductionmentioning
confidence: 99%
“…1c). In this electrode system, the positions of all electrodes were assumed to produce two types of frequencies 26 .…”
Section: Realistic Head Modelmentioning
confidence: 99%
“…When two different high-frequency currents are injected on both sides of the head, a beat with an interference frequency corresponding to the difference between the two frequencies is generated. The frequency of the injected current is that the human brain cannot recognize and the difference between the two frequencies is the target frequency, and the modulation 26 of the beat Mod is stronger in the deep region than in the shallow region. The equation for beat modulation is given by…”
Section: Modulation Of Ttismentioning
confidence: 99%
See 1 more Smart Citation